Competitiveness and Performance Analysis of Indonesian Crude Palm Oil (CPO) Exports Against Malaysia in International Trade: A Case on European Markets (Netherlands and Spain) - Ainiyah Ibrahim; Sri Muljaningsih; Kiki Asmara (Al-Buhuts, 2021)
Competition and competitiveness between Indonesia and Malaysia is always interesting to study, especially in the economic field. This study aimed to analyze and find out the difference competitiveness and performance of Indonesian Crude Palm Oil (CPO) against Malaysia in the Netherlands and Spain. This study used quantitative method. The data were gathered from the total export value and the export value of CPO from 2010-2019 which were obtained from the International Trade Statistics (ITC) with the HS code 151110. The analysis technique used the Revealed Comparative Advantage (RCA) method, Constant Market share (CMS) and using the Man-Whitney statistical test. The results showed that the average RCA value for Indonesia shows a higher value than Malaysia (47,005> 37,152), while in Spain, the average RCA index value for Indonesia is below Malaysia (68,291 <91,1458). The effect of standard growth and commodity effects on Indonesia's CPO export performance is lower than Malaysia. On the market distribution effect and the competitiveness effect in the Netherlands, Indonesia is still lower than Malaysia. while in Spain, Indonesia is higher than Malaysia. The Man-Whitney test results show that it fails to reject H0, which means that there is no significant difference between the competitiveness and performance of Indonesian CPO against Malaysia in the Netherlands and Spain.